Reconstruction of Cultural Practices in the Community: a Pedagogical Experience (2013)
AbstractThis paper reports a pedagogical experience carried out with ninth semester students from the Modern Languages Program at theUniversidad Pedagógica y Tecnológica de Colombia. The experience was conducted while the students were taking the English Language Seminar course. The main objective of this pedagogical experience was to identify future student teachers’ perceptions about sociocultural factors indifferent schools and neighborhoods in Tunja, as a way to sensitize them for their upcoming teaching practices. The data was collected by means of surveys, unstructured interviews and students’ reflective journalswith the aim to determine socio cultural factors that influence students’ learning processes. Lastly, this pedagogical experience was an approach to characterize funds of knowledge identified as the understanding that students and teachers have about their own community as a socialenvironment, from which learning processes can be better contextualized and made relevant to a determined educational setting.Key words: funds of knowledge, critical pedagogy and cultural understanding in the classroom.ResumenEste artículo presenta una experiencia pedagógica llevada a cabo con losestudiantes de noveno semestre del programa Idiomas Modernos de laUniversidad Pedagógica y Tecnológica de Colombia. La propuesta fue desarrollada en la clase “Seminario de la Lengua Inglesa.” El principal objetivo de esta propuesta fue identificar las percepciones de los futurosdocentes sobre los factores socioculturales de diferentes colegios y barrios de la ciudad de Tunja como una estrategia de sensibilización en sus futuras prácticas de enseñanza. Los datos se recogieron pormedio de cuestionarios, entrevistas no estructuradas y diarios de los estudiantes para considerar y determinar los factores socioculturales que influencian los procesos de aprendizaje de los estudiantes.Finalmente, éste fue un acercamiento a la caracterización de bases de conocimiento identificado como la comprensión que tienen los estudiantes y docentes de su propia  comunidad como medio social, desde los cuales los procesos de aprendizaje pueden ser mejor contextualizados y hacer relevante un determinado centro educacional.Palabras clave: bases de conocimiento, pedagogía crítica y comprensión cultural en el aula.